Community Empowerment Through Household Organic Waste Conversion into Eco-Enzyme-Based Botanical Insecticides as a Sustainable Home-Garden Solution - Sulistia Ningsih; Nadya Muliandari; Alifiya Herwitarahman; Pustika Adwiyani; Baaqy Amri Annisa; Mahmudi .; Safriadi .; Wahyu Setiyadi; Dermawati Sitorus; Amelia Arum Ramadhani; Eka Widiawati Wijaya Kusuma; Gunadi . (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2026)
Household organic waste remains a serious environmental problem due to its potential to cause pollution and health disturbances. At the same time, home garden cultivation is often constrained by pest attacks and dependence on chemical pesticides. This community service program aimed to empower communities by converting household organic waste into plant-based insecticide using eco-enzyme as an environmentally friendly solution for waste management and pest control. The activity was conducted in January 2025 in Kapur Village, Kubu Raya Regency, involving a group of housewives. The program stages included pre-test, socialization, hands-on practice in producing eco-enzyme and formulating botanical insecticide, and evaluation through post-test and skills observation. The results showed a significant increase in participants’ knowledge, with the average score rising from 46.3 in the pre-test to 82.5 in the post-test, indicating an improvement of 36.2%. Participants were also able to independently produce and apply the botanical insecticide. This program provides dual benefits by reducing household organic waste and offering a safer alternative for pest management. Therefore, the program effectively enhanced community capacity and supported sustainable environmental management and household food security.